Turning away from CSDP? Franco-British bilateralism in security and defence policy - Ronja Kempin; Stefan Steinicke; Jocelyn Mawdsley (Stiftung Wissenschaft und Politik (SWP), 2010)
France and Britain are sending a new signal: 12 years after the Saint-Malo Declaration,in which they called for the establishment of the European Security and Defence Policy,in an unprecedented collaboration Paris and London have resolved to turn away fromthe CSDP for the time being. The agreements on bilateral cooperation made at theFranco-British security and defence summit on 2 November 2010 are clearly more thana savings package. In unison the two states have challenged their EU partners to enterinto clear commitments on the CSDP, and thus to clarify what can be expected from theEU in security and defence policy in the future
Keywords: 320